Contradictions and Misconceptions in the Life, Music, and Philosophy of Fela Anikulapo-Kuti - Patrick , Charles Alex (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Fela Anikulapo Kuti enjoys a colossal reputation owing to his hugely enigmatic musical talent which has generated a lot of scholarship among scholars in Africa. His rebellious musical career garnered a sea of disciples mostly among the youths in Africa. His radical and acerbic slurs and corrosive attacks on successive military and civilian governments in Nigeria brought him myriad hardships, harassments, sufferings, unlawful arrests, and fame. However, while Fela projected sublime ideas in his music, some of his rhetoric and philosophy contradict many of these ideals for which he is admired and respected. Except for a few uncritical reviews about his bohemian lifestyle and eccentricities in informal writings, many of the works done on his innovative music and virulent activism are silent or in some cases apologetic about these contradictions and misconceptions. This paper hopes to shed light on these contradictions and misconceptions to show how they problematise a healthy evaluation of his contributions to the fight for justice and human liberation. This study makes use of both primary and secondary sources of data. Fela’s views and lyrics which constitute the primary data are purposively selected from several tracks and will be subjected to close reading using content analysis as the evaluation tool. Psychoanalytic theory was used to evaluate Fela’s views to determine how some of the sublime ideals projected in his music contrasted his beliefs and philosophy. The study concludes that while Fela fought some evil with one hand, he embraced the same with the other hand.